2012
DOI: 10.1523/jneurosci.6473-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking of Cell Surface Amyloid Precursor Protein Leads to Increased  -Amyloid Peptide Production in Hippocampal Neurons: Implications for Alzheimer's Disease

Abstract: The accumulation of the β-amyloid peptide (Aβ) in Alzheimer’s disease (AD) is thought to play a causative role in triggering synaptic dysfunction in neurons leading to their eventual demise through apoptosis. Aβ is produced and secreted upon sequential cleavage of the amyloid precursor protein (APP) by β- and γ-secretases. However, while Aβ levels have been shown to be increased in AD patients’ brains, little is known about how the cleavage of APP and the subsequent generation of Aβ is influenced, or if the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 87 publications
2
32
0
Order By: Relevance
“…Treatment of primary cortical neurons with Ab results in FAK activation (Williamson et al, 2002), and aberrant activation of focal adhesion proteins mediates Ab-induced neuronal dystrophy (Grace et al, 2002;Williamson et al, 2002). In addition, APP, a potential receptor for Ab (Lorenzo et al, 2000), is found at focal contacts (Sabo et al, 2001); it colocalizes with b1 integrins in neuronal cells (Yamazaki et al, 1997), and antibody-mediated clustering of APP induces significant loss of dendritic spines (Lefort et al, 2012) and neuronal injury through FAK activation (Xu et al, 2009). We found that clustering of APP was sufficient to induce Glu MTs and both APP and caspase-2 expression were required for the formation of stable Glu MTs by Ab, suggesting that induction of MT stability by Ab is initiated by the same APP/ caspase-2/RhoA pathway that leads to neurotoxicity by Ab in neurons (Lefort et al, 2012;Pozueta et al, 2013;Troy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Treatment of primary cortical neurons with Ab results in FAK activation (Williamson et al, 2002), and aberrant activation of focal adhesion proteins mediates Ab-induced neuronal dystrophy (Grace et al, 2002;Williamson et al, 2002). In addition, APP, a potential receptor for Ab (Lorenzo et al, 2000), is found at focal contacts (Sabo et al, 2001); it colocalizes with b1 integrins in neuronal cells (Yamazaki et al, 1997), and antibody-mediated clustering of APP induces significant loss of dendritic spines (Lefort et al, 2012) and neuronal injury through FAK activation (Xu et al, 2009). We found that clustering of APP was sufficient to induce Glu MTs and both APP and caspase-2 expression were required for the formation of stable Glu MTs by Ab, suggesting that induction of MT stability by Ab is initiated by the same APP/ caspase-2/RhoA pathway that leads to neurotoxicity by Ab in neurons (Lefort et al, 2012;Pozueta et al, 2013;Troy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, APP, a potential receptor for Ab (Lorenzo et al, 2000), is found at focal contacts (Sabo et al, 2001); it colocalizes with b1 integrins in neuronal cells (Yamazaki et al, 1997), and antibody-mediated clustering of APP induces significant loss of dendritic spines (Lefort et al, 2012) and neuronal injury through FAK activation (Xu et al, 2009). We found that clustering of APP was sufficient to induce Glu MTs and both APP and caspase-2 expression were required for the formation of stable Glu MTs by Ab, suggesting that induction of MT stability by Ab is initiated by the same APP/ caspase-2/RhoA pathway that leads to neurotoxicity by Ab in neurons (Lefort et al, 2012;Pozueta et al, 2013;Troy et al, 2000). Caspases have been already implicated in the induction of apoptosis, synaptic pruning and inhibition of LTP by Ab, and caspase activity is modulated by exposures to Ab (D'Amelio et al, 2011;Hyman, 2011;Jo et al, 2011;Klaiman et al, 2008;Nikolaev et al, 2009;Pozueta et al, 2013;Troy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations